Attention-Deficit/ Hyperactivity Disorder Brain Functional Reference: Introducing an Inter-subject Consistency Measure and Dual-layer Parcellation (Journal of Information and Communication Technology, 2024)
The latest advancements in neuroimaging techniques have contributedto studying the disordered human brain, but still, there is a lack of disease-specific brain reference to localise brain seeds and standardise the comparison across studies. The current study first evaluates the inter-subject consistency across Attention-Deficit/ Hyperactivity Disorder (ADHD) in a publicly accessible resting-state functional magnetic resonance imaging (RS-fMRI) ADHD-200 dataset by proposing a new voxels similarity index (VSI) that integrates both inter-atlases flexibility (F`) from previous studies with proposed intersubjects stability (S`) measure to improve outcomes. Secondly, the study employs a dual-layer clustering-based parcellation strategy inspired by the resultant improved Master Atlas networks to examine the ADHD cerebral cortex. The suggested approach to enhancing the ADHD cortex parcellation uses spectral clustering for global structure identification, followed by hierarchical clustering for local refinements and granularity specification. The final connectivity-driven brain reference achieved an average homogeneity of 0.63, and the enhanced Master Atlas with (S’) achieved 0.35 homogeneity, surpassing the original Master Atlas with 0.27. This discovery implies that the final brain reference offers a more accurate and reliable framework to examine the connections and functions of the brain in individuals with ADHD.